Comparison of two miniaturized cardiopulmonary bypass systems regarding inflammatory response - Farag, Mina; Arif, Rawa; Szabó, Gábor; Kallenbach, Klaus; Ruhparwar, Arjang; Karck, Matthias; Brenner, Thorsten; Hofer, Stefan; Weymann, Alexander (Artificial organs, 2017)
Cardiopulmonary bypass (CPB) is a known mediator of systemic inflammatory response. Extracorporeal circulations are undergoing continuous modifications and optimizations to achieve better results. Hence we aim to compare the inflammatory response associated with two recent miniature extracorporeal circulation systems during normothermic CPB. We measured plasma levels of cytokines including interleukin (IL)-1β, IL-6, IL-10, tumor necrosis factor-α, migration inhibitory factor (MIF), receptor for advanced glycation endproduct, and cluster of differentiation 40 ligand in 60 consecutive patients during the first 24 h after CPB. The patients were prospectively randomized to one of three trial groups: patients in group A were operated with the minimal extracorporeal circulation circuit (MECC, Maquet, Rastatt, Germany), group B operated with the extracorporeal circulation circuit optimized (ECC.O, Sorin, Italy), and group C operated with a conventional extracorporeal circuit (CECC, Maquet). Arterial blood samples were collected at intervals before, 30 min after initiation, and after termination of CPB. Further samples were collected 6 and 24 h after CPB. IL-10 levels were significantly raised in the CECC group as compared with either of the mini ECC-circuits with a peak concentration at 6 h postoperatively. Human MIF concentrations were significantly higher in the CECC group starting 30 min after CPB and peaking at the end of CPB. The overall reduction in cytokine concentrations in the mini-ECC groups correlated with a lower need for blood transfusion in MECC and a shorter mechanical ventilation time for ECC.O. Normothermic CPB using minimally invasive extracorporeal circulation circuits can reduce the inflammatory response as measured by cytokine levels, which may be beneficial for perioperative preservation of pulmonary function and hemostasis in low risk patients.
First published: 22 September 2016
Gesehen am 27.11.2018